ANALISIS PERSEDIAAN BAHAN BAKU KELAPA PADA PT. DIMEMBE NYIUR AGRIPRO (DNA) DI DESA TETEY, KECAMATAN DIMEMBE, KABUPATEN MINAHASA UTARA. - Antonius ., Anny; Agnes Estephina Loho; Tommy Ferdy Lolowang (AGRI-SOSIOEKONOMI, 2016)
This study aimed to analyze the level of raw material inventory coconut optimal in order to minimize the total cost of inventory during 2015 on coconut flour mill PT. Dimembe Nyiur Agripro (DNA). This research was conducted in April 2016 to June 2016, from preparation to preparation of the report. The data used is data Primary and Secondary Data. This research was conducted by interview directly to the staf of production department of PT. Dimembe Nyiur Agripro (DNA) and also use the written data in the form of documents obtained from the company. Data analysis was performed using Economic Order Quantity (EOQ). These results indicate that the optimal raw material inventory for each purchase / reservation for 2015 should be carried out by PT. Dimembe Nyiur Agripro (DNA) is 61.307 kg with 203 times the purchase frequency and interval of purchase / reordering is 2 days. Thus, companies can minimize the total cost of inventory.